2022
DOI: 10.1039/d2nj03242b
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule induces mitochondrial impairment in colon cancer cells

Abstract: Mitochondrion is one of the most important organelles controlling multiple diverse biological phenomena. Consequently, dysfunction in mitochondria leads to the initiation, development and progression of cancer, especially colon cancer. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Moreover, this 3‐methoxy‐pyrrole killed drug resistant MDA‐MB‐231 triple negative breast cancer cells and OVCAR8 ovarian cancer cells. Interestingly, from the same 3‐methoxy‐pyrrole library, we identified compound 5 which showed remarkable cell killing ability in colon cancer cells while compound 3 showed much less cell killing effect with minute structural modifications [26] . On the other hand, in this work, we identified compound 3 which is capable of killing breast cancer cells while compound 5 showed much moderate ability to kill them.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Moreover, this 3‐methoxy‐pyrrole killed drug resistant MDA‐MB‐231 triple negative breast cancer cells and OVCAR8 ovarian cancer cells. Interestingly, from the same 3‐methoxy‐pyrrole library, we identified compound 5 which showed remarkable cell killing ability in colon cancer cells while compound 3 showed much less cell killing effect with minute structural modifications [26] . On the other hand, in this work, we identified compound 3 which is capable of killing breast cancer cells while compound 5 showed much moderate ability to kill them.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, from the same 3-methoxy-pyrrole library, we identified compound 5 which showed remarkable cell killing ability in colon cancer cells while compound 3 showed much less cell killing effect with minute structural modifications. [26] On the other hand, in this work, we identified compound 3 which is capable of killing breast cancer cells while compound 5 showed much moderate ability to kill them. This result clearly indicated that biological activity guided single focused library could generate lead molecules for the treatment of different types of cancers towards personalized chemotherapy regimen.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Finally, compounds 4 a–e were condensed with mono‐tosylated ethylenediamine (5 a) and mono‐dansylated ethylenediamine (5 b) in presence of catalytic acetic acid to obtain 3‐methoxy‐pyrrole enamines (6 a–i) in 79–89 % yield (Figure S3). The new aldehyde (4 e, Figure S2) and all the library members were characterized by 1 H, 13 C NMR and HR‐MS spectroscopy (Figure S4–S33) [32,33] …”
Section: Resultsmentioning
confidence: 99%